TRANSLATION METHODS IN READER’S DIGEST MAGAZINE BY STUDENTS’ OF ENGLISH DEPARTMENT AT HKBP NOMMENSEN UNIVERSITY - Della Fransiska Ginting; Rina Mariati Nainggolan; Umar Mono (Universitas Negeri Padang, 2018)
This study aims at analyzing the types of translation methods in reader’s digest magazine translation by English department students of HKBP Nommensen University. It was designed as a descriptive-qualitative research. The participant of this study is students sixth semester group A-2013 of HKBP Nommensen University. The data were collected through a test. The data analyzed using types of translation methods by Peter Newmark. Based on the results of the data analysis, the findings of this research can be stated as follows: all types of translation methods were found in translating reader’s digest magazine. There was an article in readers digest magazine that can be categoriez into 8 types translation methods namely : word for word translation method 1 (0.03%), literal translation method 12 (0.38%), adaptation translation method 4 (0.12%), free translation method 9 (0.29%), faithfull translation method 2 (0.06%), Semantic Translation 1 (0.03%), Idiomatic Translation 1 (0.03%) and communicative translation 1 (0.03%). Based on the result of the research above, the writer find many Translation methods that the students used even though the result of their interpreting is not good enough and the writer suggest that the teacherkeeps attend to students to use the good English and for develop their materials in teaching students in translating a text by using methods of translation.